2015
DOI: 10.5301/hipint.5000276
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perception of Leg Length Discrepancy Post Total Hip Arthroplasty

Abstract: Perception of a leg length discrepancy post total hip arthroplasty (THA) is one of the most common sources of patient dissatisfaction and can have a direct influence on the considered success of the operation.This research examined postoperative perception of imposed limb discrepancies in a group of THA patients compared to a group of participants with no previous hip surgery. Two subgroups of THA patients were involved: those who did not perceive a difference in limb length following THA and those that did.Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…Femoral abduction as minor as 5 degrees has been noted to induce leg length errors of up to 8 mm [19]. Additionally, a recent study found that 74% of THA patients with a LLD of greater than 5 mm perceived that difference post-operatively, with the majority of those patients reporting significantly worse pain and Oxford scores, as compared with patients who were unaware of a LLD and/or those with a LLD less than 5 mm [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Femoral abduction as minor as 5 degrees has been noted to induce leg length errors of up to 8 mm [19]. Additionally, a recent study found that 74% of THA patients with a LLD of greater than 5 mm perceived that difference post-operatively, with the majority of those patients reporting significantly worse pain and Oxford scores, as compared with patients who were unaware of a LLD and/or those with a LLD less than 5 mm [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Traditional freehand methods are associated with LLDs of between 4 and 7 mm,34–36 discrepancies that are clinically significant, as postsurgical data indicate that patients can perceive an LLD of as little as 5 mm, and such a discrepancy can be associated with increased pain and decreased Oxford scores 37. Mechanical devices such as outriggers or calipers improve outcomes but still fall below the standard for success.…”
Section: Discussionmentioning
confidence: 99%
“…Sykes et al [9] reported that for discrepancies ≥ 5 mm, a significant number of participants were aware of the difference. They also noted that the patients who underwent THA who perceived a difference in their limb lengths postoperatively had significantly worse pain and Oxford scores compared with those who perceived their limb lengths to be equal [9].…”
Section: Discussionmentioning
confidence: 99%
“…Sykes et al [9] reported that for discrepancies ≥ 5 mm, a significant number of participants were aware of the difference. They also noted that the patients who underwent THA who perceived a difference in their limb lengths postoperatively had significantly worse pain and Oxford scores compared with those who perceived their limb lengths to be equal [9]. Mahmood et al [10] reported that patients whose limbs lengthened by > 9 mm after THA had higher incidence of shoe lift use, residual hip pain, limb length discrepancy awareness, and use of walking aids [10].…”
Section: Discussionmentioning
confidence: 99%